Estudo documental acerca das cartas trocadas entre Galileo Galilei e o príncipe Federico Cesi - Gonçalves, Wilians Roberto (2018)
This dissertation proposes to study the intrinsic daily relations between Galileo Galilei who was a scientist and, the Prince Federico Cesi who financed his researches. In the literature it is possible to find other works that discuss the importance of the history of science to understand its construction throughout the historical periods, one of them is the book "The Cigoli-Galileo Codex, Science, Art and Religion in a Copernican Enigma" these relations in the Renaissance period. In this period, reason and nature come to be valued more intensely, Renaissance man, especially scientists, begin to use experimental methods and observation of nature and the universe. While in the middle ages the life of man should be centered on God - theocentristm, from the Renaissance man becomes the main character of his story. Based on studies from this period, we sought to understand the complex relations in the construction of scientific knowledge during the period of exchanges of correspondence between Galileo Galilei and Prince Federico Cesi, taking into account the influences of the Catholic Church and the society that surrounded them. This work is documentary in nature, and will be translated and analyzed 71 letters of primary source that were exchanged between Galileo Galilei and Prince Federico Cesi. In order to do so, we try to answer the following research question: What concepts in the letters exchanged between Prince Cesi and Galileo Galilei during the Renaissance collaborate in the process of building scientific knowledge? During his research and with the help of other lynxes, Galileo significantly improved the refractor telescope, and with it he observed the sunspots, the moon mountains, the Venus phases, the four satellites of Jupiter, the saturn rings and the stars of the Via Milky The new science proposed by Galileo contributed significantly to the defense of heliocentrism, one of the most popular theories of the time